2014
DOI: 10.3934/publichealth.2014.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Gates: Identifying and Managing Offenders with Attention Deficit Hyperactivity Disorder in Community Probation Services

Abstract: Research has indicated that, compared with the general population, the prevalence of offenders with ADHD in prison is high. The situation for offenders managed in the community by the Probation Service is unknown. This study aimed to bridge the gap in our knowledge by (1) surveying the awareness of probation staff about ADHD and (2) screening the rate of offenders with ADHD managed within the service. In the first study, a brief survey was circulated to offender managers working in 7 Probation Trusts in Englan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The self-reported assessment of ADHD symptoms showed that 12.9% of the participants were screened as potentially having ADHD. Overall, ADHD seemed underdiagnosed and undertreated among detained people, as suggested previously without empirical support using clinical diagnoses available in prison medical files (Young, González, et al, 2018; Young et al, 2014). As ADHD treatment leads to improved outcomes, such as reduced recidivism (Chang et al, 2016;, all detained persons with ADHD should benefit from timely and appropriate treatment.…”
Section: Main Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The self-reported assessment of ADHD symptoms showed that 12.9% of the participants were screened as potentially having ADHD. Overall, ADHD seemed underdiagnosed and undertreated among detained people, as suggested previously without empirical support using clinical diagnoses available in prison medical files (Young, González, et al, 2018; Young et al, 2014). As ADHD treatment leads to improved outcomes, such as reduced recidivism (Chang et al, 2016;, all detained persons with ADHD should benefit from timely and appropriate treatment.…”
Section: Main Discussionmentioning
confidence: 84%
“…ADHD is usually neglected among incarcerated populations (Young, Gudjonsson, et al, 2018;Young et al, 2014), although the prevalence rate of this disorder is very high in this population (Baggio, Fructuoso, et al, 2018). Untreated ADHD is likely to lead to poor outcomes, such as maladjustment to prison life and recidivism (Berryessa, 2017;González, Gudjonsson, Wells, & Young, 2016;Gordon, Williams, & Donnelly, 2012;Young et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with inmates without ADHD, inmates with ADHD symptoms demonstrate a high frequency and severity of functional impairment that worsen in proportion to the severity of their ADHD symptoms [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…ADHD is associated with early age criminality [ 1 ], a high rate of recidivism [ 2 ], and a two to three-fold increased risk of later arrest, conviction, and imprisonment [ 1 ]. While ADHD is a treatable condition best managed by a combination of appropriate medication and psychological treatments [ 3 ], among individuals in the criminal justice system ADHD remains both mis- and under-diagnosed [ 4 6 ] and consequently inadequately treated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation